Mechanics, simulation and control III : selected, peer reviewed papers from the 2013 International Conference on Mechanics, Simulation and Control (ICMSC 2013), June 22-23, 2013, Kanyakumari, India - Gupta, K. M. (Applied mechanics and materials, 2013)
Collection of selected, peer reviewed papers from the 2013 International Conference on Mechanics, Simulation and Control (ICMSC 2013), June 22-23, 2013, Kanyakumari, India. The 99 papers are grouped as follows: Chapter 1: Advanced Materials Engineering and Technologies; Chapter 2: Mechanical Engineering and Design, Applied Mechanics; Chapter 3: Electrical Engineering and Electric Machines; Chapter 4: Power System and Electronics, Energy Engineering, Its Applications; Chapter 5: Instrumentation, Measurement Technologies, Analysis and Methodology; Chapter 6: Modern Control, Automation and Robotic Engineering; Chapter 7: Manufacturing and Industrial Engineering, Management Applications; Chapter 8: Information Technologies, Communication and Networks Engineering.